Kin selection in interactions between gametes: Gamete competition, gamete limitation, and sex allocation - Myllymaa, Lauri; Lehtonen, Jussi (Frontiers in Ecology and Evolution, 2023)
Kin selection on one hand, and gamete interactions in post-ejaculatory sexual selection on the other are two major research themes that have risen to prominence over the past half century and have simultaneously developed into enormous fields of research. There is a natural connection between the two: when gametes interact with each other, very commonly many of them originate from the same parent and are thus siblings. For example, sperm competition will almost always involve competition between sibling gametes even if the interacting parents are not related each other. If parents are related to each other, the relatedness between gametes increases further. Here we discuss the relation between kin selection on one hand, and gamete competition, gamete limitation, local gamete competition, and the evolution of sex allocation on the other. To illustrate these topics, we present a novel model on sex allocation in simultaneous hermaphrodites under sperm limitation and limited, costly dispersal. We find that sperm limitation can significantly increase allocation into male function, but limited dispersal (and thus increased relatedness) does not alter sex allocation regardless of the presence of sperm limitation.